The Effect of Music on the Attention and Memory of the Second-Grade Primary School Students with Learning Disorder in Ghaemshahr city. (European Journal of Behavioral Sciences, 2018)
The purpose of this study was to investigate the effect of Music Use on the Attention and memory of second-grade primary school students with a learning disorder in Ghaemshahr city. This study was applied in terms of purpose, and in terms of method, it was a quasi-experimental research with pre-test and post-test design with a control group. The population consisted of all second-grade primary school students with a learning disorder in Ghaemshahr city, and due to the semi-experimental nature of the research, 30 subjects (15 in the experimental group and 15 in the control group) were selected as sample using simple random sampling. Data were collected using Stroop’s Attention Test and Daneman & Carpenter’s (1980) Active Memory Test. The validity and reliability of the tools were confirmed. To analyze the data, multivariate analysis of covariance (MANCOVA) and single-variable analysis of covariance (ANCOVA) tests were used. The results showed that the use of music has a significant effect on the attention and memory of second-grade primary school students with a learning disorder in Ghaemshahr. Therefore, the use of music can be effective in improving the attention and active memory of children with a learning disorder.